2017
DOI: 10.1021/acs.nanolett.7b04982
|View full text |Cite
|
Sign up to set email alerts
|

Cell–Extracellular Matrix Mechanobiology: Forceful Tools and Emerging Needs for Basic and Translational Research

Abstract: Extracellular biophysical cues have a profound influence on a wide range of cell behaviors, including growth, motility, differentiation, apoptosis, gene expression, adhesion, and signal transduction. Cells not only respond to definitively mechanical cues from the extracellular matrix (ECM) but can also sometimes alter the mechanical properties of the matrix and hence influence subsequent matrix-based cues in both physiological and pathological processes. Interactions between cells and materials in vitro can mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 103 publications
2
66
0
Order By: Relevance
“…Recent studies have shown that substrate viscoelasticity can significantly affect the behavior and function of cells . In order to mimic the mechanical response of the created soft microniche, we have determined the nonlinear viscoelastic characteristics based on oscillatory rheometer experiments of LS hydrogels for a range of temperatures between 25–40 °C by using the energy‐based method .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that substrate viscoelasticity can significantly affect the behavior and function of cells . In order to mimic the mechanical response of the created soft microniche, we have determined the nonlinear viscoelastic characteristics based on oscillatory rheometer experiments of LS hydrogels for a range of temperatures between 25–40 °C by using the energy‐based method .…”
Section: Resultsmentioning
confidence: 99%
“…Stem cells reside in vivo in a complex and specialized microenvironment. It is well established that the behavior of hMSCs is strongly affected by the mechanics of the extracellular matrix (ECM), such as cell adhesion, migration, polarization, and differentiation, as well as organelle organization and trafficking inside the cytoplasm . The mechanical interactions between the ECM–cell and cell–cell junctions play a key role in transmitting forces to cells in in vivo microenvironment, which can further regulate intracellular signaling pathways .…”
Section: Introductionmentioning
confidence: 99%
“…2 To accommodate small samples of irregular sizes and to avoid testing issues, such as tissue clamping and tearing in tensile testing and asymmetrical geometries for compression, nanoindentation and atomic force microscopy (AFM) use nano-to microscale probes and precise sensors to contact a surface and measure corresponding deflections. 3 These tools were initially optimized to characterize nanoscale features and properties of hard materials and have also proved useful at the protein and cell scales, [4][5][6] but researchers interested in materials for biomedical applications are often interested in the mesoscale (100 mm-1 cm) as they design higher-order structures for implantation and repair.…”
Section: Introductionmentioning
confidence: 99%
“…Material´s biophysical cues, namely topography and mechanical properties, are key parameters in the regulation of stem cell behavior 44,63 . Regarding mechanical properties in particular, there is an increasing body of evidence supporting the concept that mesenchymal stem cells are extremely sensitive to tissue--level elasticity and that these physical cues are transduced into lineage specification 43,67 . Therefore, considering the significantly different physicochemical properties of the developed nanocomposite hydrogels, we evaluated its impact on cell cytoskeleton organization, spreading and gene expression as a preliminary indication of stem cell preferential differentiation pathways.…”
mentioning
confidence: 99%